What are campaigns for? the role of persuasion in electoral law and politics - Gardner, James A., 1959- (New York ; Oxford : Oxford University Press, 2009)
The author explores the contemporary American ideal of democratic citizenship in election campaigns by tracing it to its historical sources, documenting its thorough infiltration of legal norms, evaluating its feasibility in light of the findings of empirical social science, and testing it against the needs of democratic theory.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Political campaigns -- United States; Election law -- United States